Occurrence of cymothoid isopod from Miri, East Malaysian marine fishes - Anand Kumar, A.; Rameshkumar, G.; Ravichandran, S.; Priya, E.; Ramasamy, Nagarajan; Leng, A. (2015)
To identify the isopod parasite, which has been recorded from Miri, East Malaysian marine fishes. During the present study, four cymothoid isopods are reported three genera, including Cymothoa eremita, Lobothorax typus, Nerocila longispina and Nerocila loveni. Nerocila longispina and N. loveni are also previously reported from Malaysia and two additional cymothoids C. eremita and L. typus are reported for the first record of Miri coast, East Malaysia. New hosts were identified for N. loveni on Chirocentrus dorab for the first time in the world fauna. The Parasitological indexes were calculated. The site of attachment of the parasites on their hosts was also observed. These parasites can cause the damage in gill, eye and internal organ including swim bladder. Marine fish parasitology is a rapidly developing field of aquatic science.